THE PREDICTIVE ROLE OF THE HEALTH BELIEFS IN DIFFERENT FORMS OF ADAPTIVE BEHAVIOR RELATED TO THE COVID-19 - Khachatryan, N.G.; Grigoryan, A.K. (Modern Psychology, 2022)
Health campaigns and educational programs have recently focused on forming people’s beliefs. Many studies show that beliefs contribute to the development of preventive health behaviors. The purpose of this study was to investigate the predetermining role of health beliefs about Covid-19 (i.e., health belief model) for adaptive behaviors related to the pandemic. We focused on preventive, hoarding, and helping behaviors as common reactions toward the pandemic. The study was based upon a sample of 237 participants (64,1% woman, M=29,75; SD=10,693; Range=18-58). Data collection occurred between May and June 2020 through an online survey. The results of the hierarchic regression analysis showed that the preventive behavior was determined by sex, beliefs about the effectiveness of the preventive behavior, perception of barriers, perception of severity and fear of Covid-19. The economic status and beliefs of gaining prevention were significant predictors for hoarding behavior. The sex, fact of being infected, and the fear of Covid-19 predicted the helping behavior. None of the health beliefs was a predictor for this behavior. The results of the study provide an opportunity to understand the role of health beliefs about Covid-19 and other factors in the manifestation of different behaviors.